Transcriptome profiling of Curcuma longa L. cv. Suvarna - Ambika Sahoo; Basudeba Kar; Suprava Sahoo; Asit Ray; Sanghamitra Nayak (Genomics Data, 2016)
Turmeric is an economically valued crop, because of its utility in the food, pharmaceutical industries and Ayurvedic medicine, attracts the attention in many areas of research work. In the present study, we executed resequencing through transcriptome assembly of the turmeric cultivar Suvarna (CL_Suv_10). Resequencing of Suvarna variety has generated 5 Gbases raw data with 75 bp paired-end sequence. The raw data has been submitted to SRA database of NCBI with accession number SRR4042181. Reads were assembled using Cufflinks-2.2.1 tool which ended up with 42994 numbers of transcripts. The length of transcripts ranged from 83 to15565, with a N50 value 1216 and median transcript length 773. The transcripts were annotated through number of databases. For the first time transcriptome profiling of cultivar Suvarna has been done, which could help towards identification of single nucleotide polymorphisms (SNPs) between Suvarna and other turmeric cultivars for its authentic identification.